Soot Particulate Emission from A Single Cylinder Direct Injection Diesel Engine - Affina Andi, Nurul; Mohd Faizal Wan Mahmood, Wan; Ibrahim, Fadzli; Nizam Ab Rahman, Mohd (International Journal of Engineering and Technology, 2019)
Soot formation, which occurs mainly because of imperfect combustion, affects engine. Engine components tend to wear hence reduce engine performance. In the present study, soot particle collection and analysis was carried out in a relatively simple and low-cost method. The first objective is to identify the level of opacity percentage of the soot at different engine speeds and loads. The second objective is to obtain the mass of soot using Alkidas theory. The last objective is to measure and obtain the size of soot particles. The opacity was measured using a Bosch Gas Analyser and soot particles from the engine were simultaneously collected using TEM grids inserted into the exhaust manifold. Alkidas’s correlation was used to convert soot opacity to soot mass. The TEM instrument was used to produce images of the collected soot particles and at once, enable the measurement of the size of the particles. The results from this study shows that, soot opacity and mass emitted increase as the engine speed and load increase. It was observed that soot particle size become smaller at higher engine speeds and loads. From TEM image analyses, the range of size of soot obtained is 26 nm to 84 nm.
Keywords: diesel engine; opacity; soot mass; soot size; TEM